Applied Concepts in PBPK Modeling: How to Extend an Open Systems Pharmacology Model to the Special Population of Pregnant Women. (20th April 2018) - Dallmann, André; Solodenko, Juri; Ince, Ibrahim; Eissing, Thomas
Abstract : This tutorial presents the workflow of adapting an adult physiologically based pharmacokinetic (PBPK) model to the pregnant populations using the Open Systems Pharmacology (OSP) software suite (www.open-systems-pharmacology.org ). This workflow is illustrated using a previously published PBPK model for metronidazole that is extrapolated to pregnancy by parameterizing and extending the model structure in terms of pregnancy‐induced physiological changes. Importantly, this workflow can be applied to other scenarios where PBPK models need to be re‐parameterized or structurally modified.